Synthesis and characterization of multidentate iminopyridine and polypyridine transition metal complexes - McDaniel, Ashley M., author; Shores, Matthew, advisor; Anderson, Oren, committee member; Borch, Thomas, committee member; Finke, Richard, committee member; Rickey, Dawn, committee member (Colorado State University. Libraries, 2013)
The work described in this dissertation details the syntheses and characterization of transition metal complexes featuring polypyridyl and iminopyridine ligands. The primary focus has been the synthesis of 3d metal complexes of multidentate iminopyridine ligands bearing functionalizations relevant to spin crossover and photochemistry. These seemingly disparate areas of research are linked by the facts that subtle metal-ligand interactions play enormous roles in determining complex properties and that understanding these types of interactions is crucial for eventual property control. In Chapter 1, the underpinnings of spin crossover in transition metals with d4-d7 configurations are discussed along with progress toward linking spin-switching events with host-guest interactions in solution. My research on Fe(II) hexadentate iminopyridine complexes is placed into context with extending anion sensing to biologically and environmentally relevant media. Also in Chapter 1, my work on hexadentate iminopyridine and polypyridine Cr complexes is related to the current understanding of the excited state behavior of 3d iminopyridine complexes, specifically, and 3d aromatic diimines in general. Additionally, the redox non-innocence of iminopyridine and polypyridine ligands is discussed. In Chapter 2, the preparation and characterization of a series of divalent 3d transition metal complexes (Cr to Zn), featuring an ester functionalized multidentate, tripodal iminopyridine Schiff-base L5-OOMe is reported. X-ray structural studies reveal complex geometries ranging from local octahedral coordination to significant distortion towards trigonal prismatic geometry to heptacoordinate environments. Regardless of coordination mode, magnetic and spectroscopic studies show the ligand to provide moderately strong ligand fields: the Fe complex is low-spin, while the Co and Mn complexes are high-spin at all temperatures proved. Cyclic voltammograms exhibit multiple reversible ligand-based reductions, which are relatively consistent throughout the series; however, the electrochemical behavior of the Cr complex is fundamentally different from those of the other complexes. Time-dependent (TD) DFT and natural transition orbital (NTO) computational analyses for the ligand, its anion, and complexes were provided by Prof. Anthony Rappé: the computed spectra reproduce the major differential features of the observed visible absorption spectra, and NTOs provide viable interpretations for the observed features. The combined studies indicate that for Mn-Zn complexes, neutral ligands are bound to M(II) ions, but Cr is best described as a Cr(III) species bound to a radical anionic ligand. In Chapter 3, the syntheses and characterizations of Fe(II) complexes of hexadentate ligands poised for anion-triggered spin-state switching in polar solution media are reported. The tripodal iminopyridine ligands L5-OH, L6-OH and L5-ONHtBu, L6-ONHtBu contain methanolic or t-butylamide functional groups, respectively. Solid-state evidence for anion-cation hydrogen bonding interactions are observed for halide complexes of [Fe(L6-OH)]2+ and [Fe(L5-ONHtBu)]2+; [Fe(L5-ONHtBu)]2+ forms a preorganized pocket which strongly binds Cl-. Strong anion binding events in the 5-position complexes are also observed in solution via 1H NMR monitored chloride titrations in acetonitrile. And while no temperature dependence or anion dependence on spin-state is apparent for 6-position complexes in solution, a small but significant increase in magnetic susceptibility is observed for [Fe(L5-ONHtBu)]2+ as up to one equivalent of tetrabutylammonium chloride is added; suggesting that spin-state control by anion-cation interactions may be accessible for this class of compounds. In Chapter 4, the preparation and characterization of homo- and heteroleptic Cr(III) coordination complexes featuring the dimethyl 2,2'-bipyridine-4,4'-dicarboxylate (4-dmcbpy) ligand are discussed. Static and nanosecond time-resolved absorption and emission properties of these complexes dissolved in acidic aqueous (1 M HCl(aq)) solutions were investigated by Huan-Wei Tseng and Prof. Niels Damrauer. The photophysical data suggest that in these acidic aqueous environments these complexes store ~1.7 eV for multiple microseconds at room temperature. The electrochemical properties of these polypyridyl complexes were investigated by cyclic voltammetry. It is found that inclusion of 4-dmcbpy shifts the 'CrIII/II' E1/2 by +0.22 V compared to those of homoleptic parent complexes. The electrochemical and photophysical data allow for excited state potentials to be determined: for [Cr(4-dmcbpy)3]3+, CrIII*/II lies at +1.44 V versus Fc+/0 (~+2 V vs NHE), suggesting it would act as one of the most powerful photooxidants reported. In Chapter 5, the preparation, photophysical characterization, and computed excited state energies for Cr(III) complexes of a family of tripodal hexadentate and tris(bidentate) iminopyridine ligands are reported. Cyclic voltammograms reveal that the hexadentate and tris(bidentate) analogues have almost identical reduction potentials, and overall electrochemical behavior similar to the polypyridyl complexes described in Chapter 3. The absorption spectra of the hexadentate complexes show improved absorption of visible light compared to the tris(bidentate) analogues. Photophysical characterization provided by Huan-Wei Tesng and Prof. Niels Damrauer show a doublet excited state with 17 to 19 μs lifetime at room temperature for the ester functionalized tris(bidentate) complex, while no doublet states are observed for the ester functionalized hexadentate analogue under the same conditions. The electronic structure contributions to the differences in observed photophysical properties are compared by extensive computational analyses provided by Prof. Anthony Rappé. These studies indicate that the presence of non-ligated bridgehead nitrogen atoms in the complexes of tripodal hexadentate iminopyridines significantly reduce excited state doublet, quartet, and sextet energies and change the character of the low lying doublet states in compared to species that show population of doublet excited states. In Chapter 6 the syntheses and characterization of reduced forms of Cr complexes of 4-dmcbpy (described in Chapter 4), [Cr(4-dmcbpy)3]n+ (n = 2, 1), and tren(py)3 (L1, described in Chapter 5) [Cr(tren(py)3)]n+ (n = 2) are reported. Comparison of electrochemical data for the series (n = 3, 2, 1) and solid state structures of the divalent complexes are consistent with consecutive reducing equivalents added to Cr polypyridine or iminopyridine complexes not residing on the metal, and that these complexes are best described as Cr(III) ions ligated to anionic radical ligands. Final remarks about the work in Chapters 2-6 and suggested directions for future work are presented in Chapter 7.